Analysis of Multiple-Choice Questions In Musculoskeletal Module At orthopaedics and Traumatology Division, Syarif Hidayatullah State Islamic University Faculty of Medicine - Bisatyo Mardjikoen; Ahmad Mu’taz Shobary; Achmad Zaki; Marita Fadhilah; Siti Nuraisyah Jauharoh; Ahmad Azmul A. Irfan (International Journal of Health and Pharmaceutical (IJHP), 2026)
Background : Multiple choice question are a form of assessment to measure student competence. The quality of the multiple choice items can be determined using the parameters of the difficulty item, discrimination index, and distractor efficiency. Objective: To carry out item analysis of MCQs and the association between distractor efficiency with difficulty index and discrimination index in Musculoskeletal Module at Orthopaedic and Traumatology Division, Syarif Hidayatullah State Islamic University Faculty of Medicine, Jakarta, in 2018 - 2019. Methods: Observational analytic study with cross sectional design. Total samples analyzed were 155 items with 620 distractors. Results: The difficulty index showed 12 (7.75%) difficult items, 52 (33,55%) moderate items, and 91 (58,7%) easy items. Out of 155 items, 89 items (57.4%) were good questions and 66 items (42.6%) were poor questions, based on discrimination index. Eight items (5.2%) had high distractor efficiency, whereas the distractor efficiency of 73 items (47.1%), and 74 items (47.7%) were moderate and low, respectively. The functional distractors were 247 (39.8%) and non functional distractors were 373 (60.2%). There was a significant association between the distractor efficiency with difficulty index and discrimination index (p